The effect of protected lysine-methionine on gain and health of newly arrived calves - Brazle, F.K.; Stokka, Gerald L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Long-hauled calves averaging 293 lb were allotted to groups fed with or without protected lysine-methionine (Smartamine ML®). Protected lysine-methionin e did not improve ADG in the first 28 days but did improve ADG from 29 to 56 days. It also reduced morbidity (16.1 vs 34.2%) from day 29 to 56. Based on this research, the response of long-hauled calves to protected lysine-methionine in the diet appears to occur after they have recovered from the stress of shipment.
Keywords: Beef; Lysine; Methionine; Protected amino acids; Stocker calves